EFFECT OF DETONATION WAVE ON BUILDING STRUCTURES - Abdullaev Ibrohim Numanovich (Journals Park Publishing, 2022)
The influence of a detonation wave on the structures of buildings and structures has been studied for many years using the developed gas detonation unit, which makes it possible to cause artificial ground vibrations. The basics of the technique and the scheme of the experiments are presented. The principle of operation of a gas detonation unit that causes a detonation wave is described, and schemes of the impact of these waves on the structures of selected buildings are given. A method for controlling the frequency and strength of the induced vibrations by choosing the composition and amount of the combustible mixture for the gas detonation unit is highlighted. With the use of modern electronic equipment, as well as the chosen methodology and schemes for conducting experiments, a group of objects is observed that differ in design features and material. Preliminary results are given based on the data obtained.
Keywords: Structures of buildings, seismic stability, paraseismic forces, detonation wave, ground vibrations, gas detonation unit.